Analisis Service Excellent di PT. BPRS Lantabur Tebuireng Jombang Ditinjau dari Islamic Business Ethics - Indah Purnama Sari; Athi’ Hidayati (edujavare, 2023)
In this modern era, every company engaged in the service sector competes in excellence, often in the form of superior service, especially in the frontliner. To do their job well. The frontliner needs to be equipped with the ability and skills in serving customers about the basics of good service so that customers who are served are more satisfied. Because it is the frontliner who will be the spearhead in providing good service to customers so that the customer feels satisfied and the customer isencouraged to be dedicated. Of course, this must be done with excellent customer service and in accordance with the ethical principles of the Islamic company.This study aims to determine the. Analysis of Service Excellence at PT. BPRS Lantabur Tebuireng Jombang: A Perspective from Islamic Business Ethics. This research includes studies conducted in the field.while this study is designed to be qualitative and descriptive Data sources. This study contains two primary data and two secondary data. The data is recorded in this study It is done by cataloging pertinent books and materials. All collected data is processed through inductive analysis. According to the study's findings, it is possible to conclude that the adoption of aptitude, attitude, appearance, attention, action, and responsibility (accountability) for six indications of outstanding service at PT BPRS Lantabur Tebuireng Jombang, it turns out that the appearance portion is still lacking in the rest has been applied properly.In terms of Islamic business ethics, there are 4 principles that need to be guided, namely unity, justice, free will and responsibility and have implemented the 4 principles.